2023
DOI: 10.1002/ffj.3739
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic reactions towards aldehydes: An overview

Abstract: Many aldehydes are volatile compounds with distinct and characteristic olfactory properties. The aldehydic functional group is reactive and, as such, an invaluable chemical multi‐tool to make all sorts of products. Owing to the reactivity, the selective synthesis of aldehydic is a challenging task. Nature has evolved a number of enzymatic reactions to produce aldehydes, and this review provides an overview of aldehyde‐forming reactions in biological systems and beyond. Whereas some of these biotransformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 230 publications
(485 reference statements)
0
3
0
Order By: Relevance
“…The ionization state of molecules and the pH gradient across membranes are essential factors in regulating transport processes (Aoi and Marunaka, 2014). The ionization state and conformation of the active site of enzymes, influencing their catalytic efficiency (Schober et al, 2023). Hassan and Bakhiet (2017), reported that the fungus A. fumigatus cultured at pH 7, produces the strongest antibacterial compound tested against Salmonella typhimurium, Listeria monocytogenes, and Pseudomonas aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
“…The ionization state of molecules and the pH gradient across membranes are essential factors in regulating transport processes (Aoi and Marunaka, 2014). The ionization state and conformation of the active site of enzymes, influencing their catalytic efficiency (Schober et al, 2023). Hassan and Bakhiet (2017), reported that the fungus A. fumigatus cultured at pH 7, produces the strongest antibacterial compound tested against Salmonella typhimurium, Listeria monocytogenes, and Pseudomonas aeruginosa.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few years, enzymatic processes have also gained relevance in the production of aldehydes, especially in the production of vanillin. 12–15 Biological production of aldehydes offers a key advantage through its implementation of mild and comparably green reaction conditions. However, these in vivo enzymatic methods often suffer from moderate yields, a result of rapid interconversion to the corresponding alcohols or carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is a renewable, nonflammable, nontoxic, and readily available C1 source. , Over the years, CO 2 has been captured and utilized in a variety of ways such as conventional capture, oxyfuel capture, precombustion capture, postcombustion capture, and cryogenic CO 2 capture. In addition, CO 2 was used in the CO 2 -philes, which were further used to develop surfactants and chelating agents. Furthermore, CO 2 is an efficient C1 feedstock in the synthesis of various chemicals such as formic acid, urea, methanol, cyclic carbonates, oxazolidine, urethanes, polycarbonates, benzimidazole, quinazoline, etc. Previously, phosgene methods were used for the synthesis of benzimidazole and quinazoline, but there were so many limitations that this method is now replaced by the catalytic process. The biggest hurdle for CO 2 fixation in value-added products is kinetic inertness and thermodynamic stability. Furthermore, kinetic inertness and catalytic pathways such as homogeneous, heterogeneous, photochemical, radiochemical, electrochemical, thermochemical, and biochemical pathways have been used. Thiols, halohydrocarbons, olefins, and amines are nucleophilic and N-heterocyclic compounds that are biocompatible and used in the medical industry. In addition, they are also used in plant growth regulators. Benzimidazole and quinazoline are important N-heterocyclic compounds that are widely used as the intermediate substrates for which C–N, C–S, C–C, and C–O bonds are formed via CO 2 .…”
Section: Introductionmentioning
confidence: 99%